Analisis Faktor yang Berhubungan dengan Karakteristik Kehamilan Remaja di Wilayah Kerja UPT Puskesmas Kampung Kawat - Karyawati; Siti Fadhilah; Fatya Nurul Hanifa (IJMT : Indonesian Journal of Midwifery Today, 2026)
Background: Adolescent pregnancy remains a reproductive health problem in Indonesia and contributes to maternal and neonatal morbidity. In West Kalimantan Province, the prevalence of adolescent pregnancy increased from 27.4% in 2021 to 29% in 2022. Adolescent pregnancy is associated with low birth weight, preterm birth, asphyxia, infection, and psychosocial problems.Objective: This study aimed to analyze factors associated with the characteristics of adolescent pregnancy.Methods: This quantitative analytic study used a cross-sectional approach and was conducted in the working area of UPT Puskesmas Kampung Kawat from December 2023 to June 2024. The population consisted of adolescent mothers aged 14–19 years who had experienced pregnancy and childbirth,totaling 71 respondents. A sample of 42 respondents was selected using stratified random sampling. Independent variables included educational level, parental income, knowledge level, parental role, peer role, health worker role, and social media exposure. Data were collected using validated structured questionnaires and analyzed using Fisher’s Exact Test and Spearman’s Rho with a significance level of p<0.05.Results: Educational level (p=0.007), knowledge level (p<0.001), and peer role (p=0.004) were significantly associated with adolescent pregnancy characteristics. Meanwhile, parental income (p=1.000), parental role(p=1.000), health worker role (p=0.172), and social media exposure (p=0.481) were not significantly associated.Conclusion: Educational level, reproductive health knowledge, and peer role were significantly associated with adolescent pregnancy characteristics. Strengthening reproductive health education and peer educator programs is necessary to reduce risky sexual behavior among adolescents.